Security by other means : foreign assistance, global poverty, and American leadership - Brainard, Lael (Brookings Institution Press, 2007)
"Assesses the current structures of foreign assistance and makes recommendations for efficient coordination. Drawing on expertise from the full range of foreign aid agencies, examines foreign assistance across four categories: security, economic, humanitarian, and political"--Provided by publisher